Improving the Ability in Writing Narrative Text of Junior High School Students through Peer Feedback - Mochammad Noor (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
This study employed classroom action research to investigate the impact of peer feedback strategy towards the improvement of eighth graders’ ability in writing narrative text. Planning, implementing, observing, and reflecting were conducted in one cycle that consisted of 7 meetings in which, 6 meeting for implementing the stages of peer feedback strategy, and 1 meeting for conducting the writing test. The result showed that students’ average score improved 13.86 points from the preliminary study result and got 91.2% positive responds from the students after this strategy had been implemented.